1998
DOI: 10.1086/311620
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Burst 980329 and Its X-Ray Afterglow

Abstract: GRB 980329 is the brightest gamma-ray burst detected so far with the Wide Field Cameras aboard BeppoSAX, both in gamma-rays and X-rays. With

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…It has also been shown for several BeppoSAX bursts that the 2-10 keV flux at the end of the GRB phase, on time scale of tens of seconds, is close to that obtained by extrapolating backward in time the X-ray afterglow flux (e.g. Costa et al 1997, In 't Zand 1998. This suggests that the late GRB flux is in fact dominated by afterglow emission, i.e.…”
Section: Electron Energy Fractionsupporting
confidence: 71%
“…It has also been shown for several BeppoSAX bursts that the 2-10 keV flux at the end of the GRB phase, on time scale of tens of seconds, is close to that obtained by extrapolating backward in time the X-ray afterglow flux (e.g. Costa et al 1997, In 't Zand 1998. This suggests that the late GRB flux is in fact dominated by afterglow emission, i.e.…”
Section: Electron Energy Fractionsupporting
confidence: 71%
“…We performed a spectral analysis of the prompt emission of GRB 990510 in the 70È650 keV band by following approximately the same procedure used for, e.g., GRB 970228 and GRB 980329 (see Frontera et al 1998 ;in Ït Zand et al 1998). The average spectrum of the prompt emission of GRB 990510 can be satisfactorily described (s2 \ 6.84 for 9 degrees of freedom [dof]) by a broken power law, with a break energy keV and E break \ 200^27 power-law indices before and after the break of [1.36^0.16 and [2.34^0.24, respectively.…”
Section: Prompt C-ray Emissionmentioning
confidence: 99%
“…We performed a spectral analysis of the prompt emission of GRB990510 in the 70-650 keV band, by following approximately the same procedure used for, e.g., GRB970228 and GRB980329 (see Frontera et al 1998;In 't Zand et al 1998). The average spectrum of the prompt emission of GRB990510 can be satisfactorily described (χ 2 = 6.84 for 9 d.o.f.)…”
Section: Prompt γ-Ray Emissionmentioning
confidence: 99%
“…Likely the GRB released energy has almost completely ionized the initially absorbing cloud (Lazzati & Perna 2002). In this scheme however we would expect to see the optical counterpart, as in the case of GRB980329 (Palazzi et al 1998), which also showed an initial high absorption (Frontera et al 2000), and even a column density a factor 10 higher than the Galactic one during the afterglow phase (In 't Zand et al 1998). Thus a likely explanation of the GRB010214 darkness could reside in an intrinsic faintness of the related OT and/or the high GRB redshift (centroid value of 4.5) estimated by us.…”
Section: Discussionmentioning
confidence: 91%